Charmed. The complete fourth season [videorecording (DVD)] - Burge, Constance M. (Paramount Pictures, 2006)
As Piper and Phoebe struggle with the loss of their older sister, they discover the existence of half-sister Paige Matthews. Possessing the power to orb as a half-Whitelighter, Paige joins the Halliwell sisters to recreate the magical triad that protects the innocent and vanquishes evil.